Method for manufacturing solid electrolyte layer

JP7639674B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021204838
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-17
Publication Date
2025-03-05
Estimated Expiration
2041-12-17

AI Technical Summary

Benefits of technology

【0008】 本開示においては、全固体電池の抵抗を低減できる固体電解質層の製造方法を提供できるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639674000003
    Figure 0007639674000003
  • Figure 0007639674000004
    Figure 0007639674000004
  • Figure 0007639674000001
    Figure 0007639674000001
Patent Text Reader

Abstract

To provide a manufacturing method of a solid electrolyte layer which enables the reduction in resistance of an all-solid battery chiefly.SOLUTION: The above problem is solved by providing a manufacturing method of a solid electrolyte layer to be used for an all-solid battery in this disclosure. The manufacturing method of a solid electrolyte layer comprises: a preparation step of preparing a slurry containing a solid electrolyte, a binder and a dispersion medium; a setting step of setting a support body having pores on a first mold releasing film; a coating step of coating the support body with the slurry to impregnate the slurry into the support body; a drying step of drying the support body coated with the slurry to remove the dispersion medium; and a press step of setting a second mold releasing film on a face of the support body having gone through the drying step on the side opposite to the first mold releasing film, and pressing the first mold releasing film, the support body and the second mold releasing film in a lamination direction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a solid electrolyte layer. [Background technology]

[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.

[0003] For example, Patent Document 1 discloses a solid electrolyte sheet containing a nonwoven fabric and a solid electrolyte on and inside the nonwoven fabric as a solid electrolyte layer for use in an all-solid-state battery. Patent Document 2 discloses a separator in which crystalline oxide-based inorganic solid electrolyte particles are supported in a single layer on a nonwoven fabric as a solid electrolyte layer for use in an all-solid-state battery. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-031789 A [Patent Document 2] JP 2020-188026 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to improve the performance of all-solid-state batteries, a solid electrolyte layer capable of reducing resistance is required. The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a method for manufacturing a solid electrolyte layer capable of reducing the resistance of an all-solid-state battery. [Means for solving the problem]

[0006] In order to solve the above problems, the present disclosure provides a method for producing a solid electrolyte layer used in an all-solid-state battery, the method comprising: a preparation step of preparing a slurry containing a solid electrolyte, a binder, and a dispersion medium; a placement step of placing a support having holes on a first release film; a coating step of applying the slurry to the support to impregnate the support with the slurry; a drying step of drying the support to which the slurry has been applied to remove the dispersion medium; and a pressing step of placing a second release film on the surface of the support after the drying, opposite to the first release film, and pressing the first release film, the support, and the second release film in the stacking direction.

[0007] According to the present disclosure, a support having pores is impregnated with a slurry containing a solid electrolyte, so that a solid electrolyte layer capable of reducing the resistance of an all-solid-state battery can be produced. Effect of the Invention

[0008] The present disclosure has an effect of providing a method for manufacturing a solid electrolyte layer that can reduce the resistance of an all-solid-state battery. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a flow diagram illustrating a method for producing a solid electrolyte layer in the present disclosure. [Diagram 2] FIG. 1 is a schematic perspective view illustrating an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The method for producing a solid electrolyte layer in the present disclosure will be described in detail below.

[0011] FIG. 1 is a flow diagram illustrating a method for manufacturing a solid electrolyte layer in the present disclosure. As shown in FIG. 1, first, a slurry containing a solid electrolyte, a binder, and a dispersion medium is prepared (preparation step). Then, a support having voids is placed on a first release film (placement step). The placement step may be performed before the preparation step or simultaneously with the preparation step. Next, the slurry is applied to the support, and the support is impregnated with the slurry (coating step). Next, the support to which the slurry is applied is dried to remove the dispersion medium (drying step). Then, a second release film is placed on the surface of the support opposite to the first release film after drying, and the first release film, the support, and the second release film are pressed in the lamination direction (pressing step). This allows the production of a solid electrolyte layer placed between the first release film and the second release film.

[0012] According to the present disclosure, a support having pores is impregnated with a slurry containing a solid electrolyte, so that a solid electrolyte layer capable of reducing the resistance of an all-solid-state battery can be manufactured. In addition, since a support is used, a thin solid electrolyte layer can be manufactured, so that the resistance of an all-solid-state battery can be reduced. Furthermore, according to the present disclosure, since a support is used and densification is performed by pressing, the manufactured solid electrolyte layer is self-supporting, and handling is good when used in the manufacture of an all-solid-state battery.

[0013] 1. Preparation process The preparation step in the present disclosure is a step of preparing a slurry containing a solid electrolyte, a binder, and a dispersion medium.

[0014] (1) Solid electrolyte Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes. Examples of the inorganic solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, hydrogen boron solid electrolytes, and molten salts that are solid at room temperature. Examples of the organic solid electrolyte include flexible crystalline solid electrolytes. Among these, sulfide solid electrolytes are preferred because of their high ionic conductivity. The solid electrolyte may be one type or two or more types.

[0015] The sulfide solid electrolyte usually contains sulfur (S) as a main component of an anion element. The sulfide solid electrolyte preferably contains, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may also contain at least one of Cl element, Br element, and I element as a halogen element. The sulfide solid electrolyte may also contain O element.

[0016] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m Sn (where m and n are positive numbers. Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.)

[0017] The composition of the sulfide solid electrolyte is not particularly limited, but examples thereof include xLi2S·(100-x)P2S5 (70≦x≦80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5) (0.7≦x≦0.8, 0≦y≦30, 0≦z≦30).

[0018] The solid electrolyte may be glass (amorphous), glass ceramics, or crystals. Glass can be obtained, for example, by amorphizing raw materials. Glass ceramics can be obtained, for example, by subjecting glass to heat treatment. Crystals can be obtained, for example, by heating raw materials for the solid electrolyte.

[0019] The shape of the solid electrolyte may be, for example, particulate. The particle size (D50) of the solid electrolyte is, for example, 10 nm or more and 50 μm or less. D50 can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM). The ionic conductivity (25° C.) of the solid electrolyte is preferably high. The ionic conductivity (25° C.) of the solid electrolyte is, for example, 1×10 -4 S / cm or more, 1×10 -3 The ratio of the solid electrolyte in the solid components of the slurry is, for example, 70% by weight or more and 99% by weight or less.

[0020] (2) Binder Examples of the binder include rubber-based binders such as butylene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVdF). The binder may be one type or two or more types. The ratio of the binder in the solid components of the slurry is, for example, 1% by weight or more and 30% by weight or less.

[0021] (3) Dispersion medium Examples of the dispersion medium include esters such as butyl butyrate, dibutyl ether, and ethyl acetate, ketones such as diisobutyl ketone (DIBK), methyl ketone, and methyl propyl ketone, aromatic hydrocarbons such as xylene, benzene, and toluene, alkanes such as heptane, dimethylbutane, and methylhexane, and amines such as tributylamine and allylamine. The proportion of the dispersion medium in the slurry is, for example, 60 parts by weight or more and 120 parts by weight or less, assuming that the solid component of the slurry is 100 parts by weight.

[0022] (4) Slurry The slurry may be purchased as a commercial product or may be prepared by oneself. In the latter case, the method of preparing the slurry may include, for example, a method of kneading a composition containing a solid electrolyte, a binder, and a dispersion medium. The kneading method may include, for example, a method using a general kneading device such as a dissolver, a homomixer, a kneader, a roll mill, a sand mill, an attritor, a ball mill, a vibrator mill, a high-speed impeller mill, an ultrasonic homogenizer, or a shaker.

[0023] 2.Placement process The disposing step in the present disclosure is a step of disposing a support having holes on a first release film.

[0024] The support having voids may have a woven fabric structure or a nonwoven fabric structure. The woven fabric structure refers to a structure in which fibers (e.g., resin fibers, glass fibers) are regularly arranged, and the nonwoven fabric structure refers to a structure in which fibers (e.g., resin fibers, glass fibers) are randomly arranged. The support in the present disclosure may be a nonwoven fabric.

[0025] The porosity of the support is not particularly limited, but may be, for example, 30% or more, 50% or more, or 70% or more. On the other hand, the porosity of the support is, for example, 90% or less. The porosity of the support can be calculated from the density and true density of the support.

[0026] The thickness of the support is, for example, 10 μm or more, and may be 20 μm or more, while the thickness of the support is, for example, 50 μm or less.

[0027] The release film preferably has, for example, a film and a coating containing a release agent. Examples of the material of the film include resins such as polyethylene terephthalate (PET) and polyester. Examples of the release agent include silicone-based release agents.

[0028] The first release film preferably has a small peel strength against a predetermined tape. The peel strength of the first release film against a polyester adhesive tape (No. 31B, manufactured by Nitto Denko) is, for example, 0.15 N / 50 mm or less, and may be 0.10 N / 50 mm or less. If the peel strength is too large, defects may occur in the solid electrolyte layer when the first release film is peeled off after the pressing process described below. The peel strength can be measured, for example, by the method described in JIS Z 0237:2009 (Test method for adhesive tapes and adhesive sheets).

[0029] The thickness of the first release film is not particularly limited, but is, for example, not less than 10 μm and not more than 30 μm.

[0030] 3. Coating process The coating step in the present disclosure is a step of coating a support with a slurry to impregnate the support with the slurry, which allows the solid electrolyte to fill the pores of the support.

[0031] The method for applying the slurry is not particularly limited, but examples thereof include a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, and a bar coating method.

[0032] 4.Drying process The drying step in the present disclosure is a step of drying the support onto which the slurry has been applied to remove the dispersion medium.

[0033] The drying method is not particularly limited as long as it can volatilize the dispersion medium, and examples of the drying method include common methods such as warm air / hot air drying, infrared drying, reduced pressure drying, dielectric heating drying, etc. Examples of the drying atmosphere include an inert gas atmosphere such as an Ar gas atmosphere or a nitrogen gas atmosphere, an air atmosphere, and a vacuum.

[0034] The drying temperature is not particularly limited, but is preferably a temperature at which the solid electrolyte does not deteriorate. The drying temperature is, for example, 100° C. or higher and 200° C. or lower. The drying time is not particularly limited and can be adjusted appropriately.

[0035] 5. Pressing process The pressing step in the present disclosure is a step of placing a second release film on the surface of the support opposite to the first release film after drying, and pressing in the lamination direction of the first release film, the precursor layer, and the second release film. In the present disclosure, the pressing step can obtain a solid electrolyte layer placed between the first release film and the second release film.

[0036] The second release film is the same as the first release film described above. The second release film and the first release film may be made of the same material or different materials. The second release film and the first release film may have the same thickness or different thicknesses.

[0037] The pressing method is not particularly limited as long as it is a method that can apply pressure in the lamination direction of the first release film, the support, and the second release film. Examples of the pressing method include roll pressing and flat plate pressing. In the case of roll pressing, the linear pressure is, for example, 1 ton / cm or more and 8 ton / cm or less. Pressing may also be hot pressing.

[0038] When the produced solid electrolyte layer is used in an all-solid-state battery, the first release film and the second release film are usually peeled off.

[0039] 6.Solid electrolyte layer The solid electrolyte layer produced by the above process contains a support, a solid electrolyte, and a binder. It may also contain a dispersion medium as a residual component. The support, solid electrolyte, binder, and dispersion medium are as described above.

[0040] The thickness of the solid electrolyte layer is, for example, 10 μm or more, may be 15 μm or more, or may be 20 μm or more. On the other hand, the thickness of the solid electrolyte layer is, for example, 50 μm or less, may be 40 μm or less, or may be 30 μm or less. In addition, the Young's modulus of the solid electrolyte layer is, for example, 1 GPa or more and 100 GPa or less.

[0041] In addition, since the solid electrolyte layer in the present disclosure contains a support, it can be self-supporting, and therefore, when used in an all-solid-state battery described later, it can have a larger area in plan view than the positive electrode layer and the negative electrode layer.

[0042] 7.All-solid-state battery The solid electrolyte layer in the present disclosure is used in an all-solid-state battery. FIG. 2 is a schematic perspective view illustrating an all-solid-state battery in the present disclosure. The all-solid-state battery 10 shown in FIG. 2 has a positive electrode layer 1, a negative electrode layer 2, and a solid electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2. The solid electrolyte layer 3 is a solid electrolyte layer manufactured by the above-mentioned method. In addition, the all-solid-state battery 10 has a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2.

[0043] In the present disclosure, since the solid electrolyte layer is a solid electrolyte layer produced by the above-mentioned method, the all-solid-state battery has low resistance.

[0044] As shown in FIG. 2, in the all-solid-state battery according to the present disclosure, T When viewed in a plan view along the line, the area of ​​solid electrolyte layer 3 is preferably larger than the areas of negative electrode layer 2 and positive electrode layer 1. This is because the occurrence of an internal short circuit is suppressed.

[0045] The materials of the positive electrode layer and the negative electrode layer can be materials conventionally used in all-solid-state batteries. In addition, all-solid-state batteries usually have a positive electrode current collector that collects the current of the positive electrode layer and a negative electrode current collector that collects the current of the negative electrode layer. The materials of the positive electrode current collector and the negative electrode current collector can be materials conventionally used in all-solid-state batteries. In addition, the shapes of the positive electrode current collector and the negative electrode current collector can be appropriately adjusted.

[0046] The all-solid-state battery in the present disclosure is typically an all-solid-state lithium-ion secondary battery. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid electric vehicles or electric vehicles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.

[0047] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0048] [Example 1] (Preparation of solid electrolyte layer) The sulfide solid electrolyte was weighed out to be 99% by weight and the SBR binder to be 1% by weight. These were added to butyl butyrate so that the solid content was 55% by weight, and ultrasonically dispersed for 1 minute using an ultrasonic disperser. This produced a slurry for the solid electrolyte layer. As the sulfide solid electrolyte, 15LiBr 10LiI 75 (0.75Li2S 0.25P2S5) glass ceramics with a particle diameter (D50) of 2.5 μm measured based on the laser diffraction and scattering method were used.

[0049] Next, a polyester nonwoven fabric (thickness 25 μm, porosity 80%, MD tensile strength 5 N / cm, CD tensile strength 1 N / cm) was placed on a 25 μm thick release film (Cerapeel WZ, manufactured by Toray). The solid electrolyte layer slurry was then uniformly applied onto the nonwoven fabric by blade coating using an applicator. The basis weight was 5.0 mg / cm including the nonwoven fabric. 2 The nonwoven fabric was then dried at 100°C for 60 minutes to obtain a nonwoven fabric with the pores filled with solid electrolyte. Another release film was then placed on top of the nonwoven fabric and roll pressed at a pressure of 1 ton / cm. After pressing, the release films on the top and bottom of the support were peeled off. This resulted in a solid electrolyte layer. The obtained solid electrolyte layer was 30 μm thick and was self-supporting. Furthermore, no slurry components remained on the peeled release film, and all of the solid electrolyte was transferred to the nonwoven fabric.

[0050] (Preparation of positive electrode) The positive electrode active material is LiNi with a particle diameter (D50) of 5 μm as measured by the laser diffraction / scattering method. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 powder was used. Next, the surface of the positive electrode active material was coated with LiNbO3 using the sol-gel method. The above glass ceramics was used as the sulfide solid electrolyte. The positive electrode active material and the sulfide solid electrolyte were weighed out so that the weight ratio was 75:25. Furthermore, 3 parts by weight of SBR binder and 10 parts by weight of conductive material (CNF) were weighed out for 100 parts by weight of the positive electrode active material. These were added to butyl butyrate so that the solid content was 60% by weight, and ultrasonic dispersion treatment was performed for 1 minute using an ultrasonic dispersion device. This resulted in the positive electrode slurry.

[0051] The obtained positive electrode slurry was applied by blade coating using an applicator onto an aluminum foil (positive electrode current collector) having a thickness of 15 μm in a coating amount of 25 mg / cm. 2 The aluminum foil was coated uniformly so that the thickness of the aluminum foil was 100° C. and then dried for 60 minutes at 100° C. As a result, a positive electrode having a positive electrode layer formed on the aluminum foil was obtained.

[0052] (Preparation of negative electrode) As the negative electrode active material, Si powder having a particle diameter (D50) of 5 μm measured based on the laser diffraction scattering method was used. As the sulfide solid electrolyte, the above glass ceramics was used. The negative electrode active material and the sulfide solid electrolyte were weighed out so that the weight ratio was 50:50. Furthermore, 3 parts by weight of SBR binder and 10 parts by weight of conductive material (CNF) were weighed out for 100 parts by weight of the negative electrode active material. These were added to butyl butyrate so that the solid content was 40% by weight, and ultrasonic dispersion treatment was performed for 1 minute using an ultrasonic dispersion device. As a result, a negative electrode slurry was obtained.

[0053] The obtained negative electrode slurry was applied by blade coating using an applicator onto a copper foil (negative electrode current collector) having a thickness of 25 μm at a coating weight of 5 mg / cm. 2 The coating was then dried at 100° C. for 60 minutes to obtain a negative electrode having a negative electrode layer formed on the copper foil.

[0054] (Preparation of all-solid-state batteries for evaluation) The positive electrode layer was cut into a square shape of 4.0 cm x 4.0 cm together with the aluminum foil, the negative electrode layer was cut into a square shape of 4.0 cm x 4.0 cm together with the copper foil, and the solid electrolyte layer was cut into a square shape of 4.4 cm x 4.4 cm. These were stacked in the order of the negative electrode layer, the solid electrolyte layer, and the positive electrode layer, and roll pressed at a pressure of 3 tons / cm to obtain a laminated electrode body. The obtained laminated electrode body was sealed in an exterior body made of an aluminum laminate film to which positive and negative electrode terminals were previously attached. In this way, an all-solid-state battery for evaluation (all-solid-state lithium-ion secondary battery) was produced.

[0055] [Comparative Example 1] (Preparation of polymer solid electrolyte layer) Polyethylene oxide (PEO; Mw is about 4,000,000) and lithium bistrifluoromethanesulfonylimide (Li-TFSI) were weighed out so that the molar ratio of EO units:TFSI was 20:1. These were dissolved in acetonitrile to obtain a polymer electrolyte solution. Next, benzoyl peroxide (BPO, a radical polymerization initiator) was mixed into the polymer electrolyte solution so that the concentration was 10% by weight relative to the mixture of PEO and Li-TFSI, and the mixture was stirred until it became a homogeneous solution. The prepared solution was applied onto a release film (PET film) by a blade method using an applicator. Then, after natural drying, the mixture was dried on a hot plate at 100°C for 60 minutes. As a result, a polymer solid electrolyte layer with a thickness of 50 μm was obtained. The obtained polymer solid electrolyte layer was self-supporting.

[0056] (Preparation of all-solid-state batteries for evaluation) An all-solid-state battery for evaluation was produced in the same manner as in Example 1, except that the above-mentioned polymer solid electrolyte layer was used as the solid electrolyte layer (SE layer).

[0057] [evaluation] (Open circuit voltage measurement) The evaluation batteries prepared in Example 1 and Comparative Example 1 were restrained under a pressure of 100 MPa, and the open circuit voltage (OCV) was measured to confirm the presence or absence of a short circuit. The results are shown in Table 1.

[0058] (Resistance measurement) The evaluation all-solid-state batteries prepared in Example 1 and Comparative Example 1 were restrained under a pressure of 100 MPa, and the resistance was measured. The measurement was performed according to the following procedure. First, the batteries were CCCV charged to 4.5 V at a current rate of 16 mA (current cutoff value, 0.16 mA). Next, the batteries were CCCV discharged to 4.0 V at a current rate of 16 mA (current cutoff value, 0.16 mA). After discharge, the batteries were left to stand for 1 hour. Then, the batteries were discharged under the conditions of CC discharge, current rate of 10 mA, and 10-second cutoff, and the battery resistance was measured according to Ohm's law. The results are shown in Table 1.

[0059] [Table 1]

[0060] As shown in Table 1, the resistance of Example 1 was lower than that of Comparative Example 1. This is believed to be because the thickness of the SE layer (solid electrolyte layer) could be reduced by using a support (nonwoven fabric) having voids. In addition, it is believed to be because the solid electrolyte layer in Example 1 was pressed in the preparation of the solid electrolyte layer, resulting in a denser solid electrolyte layer. It is also believed to be because the ionic conductivity of the sulfide solid electrolyte was higher than that of the polymer solid electrolyte. In addition, in Example 1 and Comparative Example 1, the OCV was greater than 0 V, and no short circuit (internal short circuit) occurred. This confirmed that the occurrence of an internal short circuit can be suppressed by making the area of ​​the SE layer larger than the areas of the positive and negative electrodes.

[0061] [Example 2] The thickness of the nonwoven fabric was 10 μm, and the slurry was applied at a basis weight of 2.0 mg / cm 2 A solid electrolyte layer was produced in the same manner as in Example 1, except that the coating was applied uniformly so that the thickness of the solid electrolyte layer was 15 μm. The obtained solid electrolyte layer had a thickness of 15 μm and was self-supporting. In addition, no coating film remained on the peeled release film, and the entire sulfide solid electrolyte was transferred to the nonwoven fabric.

[0062] [Comparative Example 2] Without using nonwoven fabric, the solid electrolyte slurry was applied to a 25 μm-thick release film (Cerapeel WZ, Toray) with a basis weight of 5.0 mg / cm. 2 A solid electrolyte layer was produced in the same manner as in Example 1, except that the release film was uniformly applied so that the solid electrolyte layer had a thickness of 100 μm or more. The obtained solid electrolyte layer collapsed upon peeling off the release film, and could not stand on its own.

[0063] [Comparative Example 3] Except for using SUS foil instead of the release film, a solid electrolyte layer was produced in the same manner as in Example 2. The obtained solid electrolyte layer was self-supporting, but the coating film remained on the peeled SUS foil and was visible through the nonwoven fabric side.

[0064] [Comparative Example 4] After drying, except that the nonwoven fabric was peeled off from the release film without roll pressing, a solid electrolyte layer was produced in the same manner as in Example 2. The obtained solid electrolyte layer was self-supporting, but the coating film remained on the release film and the nonwoven fabric was transparent.

[0065] [Comparative Example 5] An all-solid-state battery for evaluation was produced in the same manner as in Example 1, except that the solid electrolyte layer produced in Comparative Example 4 was used as the solid electrolyte layer. The open circuit voltage of the obtained all-solid-state battery for evaluation was measured as described above, and the presence or absence of a short circuit was evaluated. The results are shown in Table 2 together with the results of Example 1 and Comparative Example 1.

[0066] [Table 2]

[0067] As shown in Table 2, in Comparative Example 5, the area of ​​the solid electrolyte layer was larger than the areas of the positive and negative electrodes, but the OCV was 0 V and a short circuit (internal short circuit) occurred. This is believed to be because the support (nonwoven fabric) could not be sufficiently filled with the solid electrolyte, resulting in insufficient insulation of the solid electrolyte layer. In Comparative Example 5, the resistance value could not be measured because an internal short circuit occurred.

[0068] In Comparative Example 5, it is possible that the occurrence of short circuits can be suppressed by making the solid electrolyte layer thicker, but it is presumed that the battery resistance increases with the increase in thickness. As shown in Comparative Example 4, the solid electrolyte layer produced without pressing could not be sufficiently filled with solid electrolyte in the nonwoven fabric, and the amount of voids in the solid electrolyte layer was large. Therefore, it is presumed that the battery resistance increases due to the increase in the degree of bending in the solid electrolyte layer and the decrease in the contact area between the solid electrolyte layer and the active material layer. [Explanation of symbols]

[0069] 1 ... Positive electrode layer 2 ... Negative electrode layer 3...Solid electrolyte layer 4...Positive electrode current collector 5 ...Negative electrode current collector 10 …All-solid-state batteries

Claims

[Claim 1] A method for producing a solid electrolyte layer for use in an all-solid-state battery, comprising the steps of: A preparation step of preparing a slurry containing a solid electrolyte, a binder, and a dispersion medium; a placement step of placing a support having holes on a first release film; a coating step of coating the slurry onto the support to impregnate the support with the slurry; a drying step of drying the support on which the slurry has been applied to remove the dispersion medium; a pressing step of placing a second release film on the surface of the support after drying opposite to the first release film, and pressing the first release film, the support, and the second release film in a lamination direction; The support is a nonwoven fabric, The porosity of the support is 70% or more and 90% or less, The method for producing a solid electrolyte layer, wherein the support has a thickness of 10 μm or more and 50 μm or less.

Citation Information

Patent Citations

  • Lithium ion secondary battery and solid electrolyte

    JP2006086102A

  • Solid electrolyte sheet and all-solid type secondary battery

    JP2016031789A

  • Solid electrolyte sheet and all-solid secondary battery

    JP2016139482A

  • Solid electrolyte slurry, method for manufacturing solid electrolyte sheet, solid electrolyte slurry inclusion body, electrode slurry, method for manufacturing electrode sheet, electrode slurry inclusion body, and method for manufacturing all-solid type lithium ion battery

    JP2019194997A

  • All-solid battery and manufacturing method thereof

    JP2020181669A